Rancang Bangun Penambahan Sistem Monitoring Suhu Pipa Inlet dan Onlet Air Handling Unit Bandar Udara Internasional Yogyakarta Berbasis Internet of Things - Wibowo, Imam Haryadi; Novariski, Muhammad Samudera; Wardana, Siddiq Sukma; Hidayat, Aldy Fahmi; Woretma, Istiqomah; Dewitasari, Melanie Putri (Jurnal Teknik Mekanikal Bandar Udara, 2023)
The number of existing air handling units coupled with the number of technician personnel and having many work assignments is one of the factors causing the difficulty of monitoring all air handling units at Yogyakarta International Airport. The aim of the research is to make it easier for technicians to monitor the AHU in real time so that when damage occurs it can be detected and further action can be taken. This study used the Research and Development (R&D) level 1 research method. Based on the results obtained, it can be concluded that the authors have succeeded in creating a temperature monitoring system in the AHU unit using the DS18B20 temperature sensor and not changing the control circuit of the air handling unit.